تحليل سياسات الحكومة في إدارة أموال الحج: تزامن القانون رقم 34 لعام 2014 مع مبادئ الشريعة الاقتصادية: Analysis of Government Policies in the Management of Hajj Funds: The Conformity of Law Number 34 of 2014 with the Principles of Economic Sharia - Prestiyono, Bagus Ledi; Alam, Azhar (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the extent of the suitability of the Indonesian government's policy in managing hajj funds based on Law Number 34 of 2014 according to the principles of sharia economics and sharia maqashid, especially the principle of maintenance and achievement of the benefits of the ummah. Methodology: This study uses a legal-normative approach with a descriptive qualitative analysis method. Data was obtained through a study of laws and regulations related to the management of hajj funds, DSN-MUI fatwas, scientific literature, as well as financial and performance reports of the Hajj Financial Management Agency (BPKH) for the period 2024 2025. The analysis was carried out by integrating a positive sharia perspective and sharia maqashid. Results: The results of the study show that Law Number 34 of 2014 provides a strong legal basis for the management of hajj funds based on sharia principles, accountability, and transparency. However, in practice, there is still a gap between formal compliance with sharia and the achievement of substantive goals of sharia maqashid, particularly in the aspects of public transparency, increased economic benefits, and equitable distribution of the social impact of hajj investments. Application/Authenticity/Value: This research makes a conceptual contribution by combining positive legal analysis and